Analysis of Erosion and Sedimentation Rates in Karian Reservoir using the USLE Method on the Reservoir's End-of-Life Capacity - Samuel Seprian Pakpahan; Sri Sangkawati Sachro; Suharyanto Suharyanto (TEKNIK, 2025)
Karian Reservoir is a multipurpose reservoir designed to meet raw water needs, provide irrigation water supply, reduce flooding, and generate micro-hydropower potential. It has a dead storage capacity of 46.4 million m³ with a projected service life of 100 years, based on the time required for sediment to fill the dead storage. The planned sedimentation rate of 579,162 m³/year was determined using an empirical formula derived from sediment curves based on tributary surveys conducted in 1995. If sedimentation exceeds dead storage capacity, the reservoir's lifespan and ability to meet water demands will be compromised, making it crucial to analyze sedimentation rates and distribution. Erosion rate analysis using the USLE method for the period 2017-2023 resulted in an average erosion rate of 1,249,177.27 tons/year, with a Sediment Delivery Ratio of 0.304 and a trap efficiency of 95%, leading to a sedimentation rate of 328,397.28 tons/year. The sediment deposition distribution over 100 years, estimated using the Empirical Area Reduction Method, indicated that the new base level would rise by 10.17 meters to an elevation of 30.17 meters. The remaining dead storage capacity is 21.12 million m³ (45.48%), with an effective storage capacity of 112.83 million m³ (96.38%). Theoretically, Karian Reservoir can still achieve its full service life..